Housing in a university situation: a study of student living - Fish, Hirsh L (School of Architecture, Planning and Geomatics, 2020)
Whilst travelling in the united states and Europe during 1969, I visited various university campuses. It was at Bochum being built at the time in Germany that I became especially aware of how separated the university community seemed to be from the society outside. Due it its remoteness I decided to examine and evaluate the relationships that exist between a university and its community preferably in some particular field of study. I drew the hypothesis that there existed a casual relationship between vehicular congestion and housing and that by providing more on campus housing a move towards alleviating the congestion problems would be made. In the gathering of information on residence provision, it became apparent that there exists an intense level f concern amongst our university administrators in regard to the correct provision of student housing and that much research work needed to be done in this field. Starting at the beginning of this year and after some considerable time, with much energy spent, the stages has been reached where the emerging problem of student housing can be defined. It is hoped that this thesis will make some contribution of the kind of housing out students want and need and that from this study a re-assessment of basic attitudes to the housing of our students can be made.